2021
DOI: 10.1089/neu.2020.7226
|View full text |Cite
|
Sign up to set email alerts
|

In VivoDetection of Extracellular Adenosine Triphosphate in a Mouse Model of Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is traditionally characterized by primary and secondary injury phases, both contributing to pathological and morphological changes. The mechanisms of damage and chronic consequences of TBI remain to be fully elucidated, but synaptic homeostasis disturbances and impaired energy metabolism are proposed to be a major contributor. It has been proposed that an increase of extracellular (eATP) adenosine triphosphate (ATP) in the area immediately surrounding impact may play a pivotal role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Some of these endogenous danger signals can induce activation of the inflammasome and the secretion of proinflammatory cytokines by innate immune cells [ 4 , 38 ]. Using transgenic mice that express luciferase on the outer layer of the cell membrane, we showed that similar to traumatic brain injury [ 39 ], eATP is released very early during ischemic tissue damage. In addition, the signal is sustained over 24 h, clearly indicating an ongoing release of eATP in the ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these endogenous danger signals can induce activation of the inflammasome and the secretion of proinflammatory cytokines by innate immune cells [ 4 , 38 ]. Using transgenic mice that express luciferase on the outer layer of the cell membrane, we showed that similar to traumatic brain injury [ 39 ], eATP is released very early during ischemic tissue damage. In addition, the signal is sustained over 24 h, clearly indicating an ongoing release of eATP in the ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Such approach could be done using available sensitive and selective biosensors expressed in microglial cells of the spinal cord. 69 , 70 , 71 Microglia express several subtypes of ionotropic (P2XRs) and metabotropic purinergic receptors (P2YRs), which detect synaptic release of ATP. 34 The nature of purinergic responses is dose-dependent; low concentrations of ATP act via P2YRs, but high concentrations (millimolar range) activate P2XRs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mammalian TBI model is more advanced in its robust research background focusing on the mechanism and important biomarkers. 117,[163][164][165][166][167][168] In addition to that, non-mammalian research has not conducted any research on inducing stem cell for brain injury as been conducted previously in this study with mammalian model. 169,170 Indeed, one of the study showed successful xenotransplantation of human iPSC-derived NSCs and isogenic neural cell progenies in a mouse model.…”
Section: Future Direction Of Non-mammalian Animal Model In Traumatimentioning
confidence: 98%